2016
DOI: 10.36487/acg_rep/1608_37_cowan
|View full text |Cite
|
Sign up to set email alerts
|

In situ bioremediation of South African coal discard dumps

Abstract: Current rehabilitation of coal discard dumps remains a challenge due to reliance on topsoil for establishment of vegetation. Fungcoal has been developed as a viable and alternative strategy for rehabilitation of coal discard dumps and opencast spoils. Fungcoal exploits fungi-plant mutualism to achieve biodegradation of weathered coal, which in turn, promotes reinvigoration of soil components, grass growth and re-vegetation. The main objective of the present study was to determine the effect of different co-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Coal discard was obtained from waste dumps in the eMalahleni coal fields, Mpumalanga Province, South Africa. Geologically weathered coal was sourced from the No.2 Seam, Kromdraai Section, Landau Colliery (Cowan et al 2016). Substrates were air-dried and ground using a HP-M 100 Pulverizer (HERZOG Maschinenfabrik GmbH Co., Osnabrück, Germany) to yield particles of approximately 0.2-0.5 mm in diameter and sterilized by freeze thawing using liquid nitrogen (three cycles) to eliminate any in situ bacterial activity.…”
Section: Preparation and Characterization Of Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coal discard was obtained from waste dumps in the eMalahleni coal fields, Mpumalanga Province, South Africa. Geologically weathered coal was sourced from the No.2 Seam, Kromdraai Section, Landau Colliery (Cowan et al 2016). Substrates were air-dried and ground using a HP-M 100 Pulverizer (HERZOG Maschinenfabrik GmbH Co., Osnabrück, Germany) to yield particles of approximately 0.2-0.5 mm in diameter and sterilized by freeze thawing using liquid nitrogen (three cycles) to eliminate any in situ bacterial activity.…”
Section: Preparation and Characterization Of Substratesmentioning
confidence: 99%
“…Land devastation in regions where coal mining has taken place is well documented and serves to emphasise the need for continued effort to develop sound rehabilitation technologies to support re-vegetation and transformation of this disturbed land to a new beneficial condition (Sheoran et al 2010;Limpitlaw and Briel 2015;Weyer et al 2017). Biological rehabilitation has become the strategy of choice and is considered to be economic, safe, more energy efficient and environmentally compatible, and potentially capable of providing a means to convert coal discard to ash and sulphurfree products of value (Reich-Walber et al 1997;Klein et al 2001;Hofrichter and Fakoussa 2001;Machnikowska et al 2002;Sekhohola et al 2013;Cowan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, it has become increasingly important to gain better insight into the molecular structure and mineral matter of coal, for both coal beneficiation and to mitigate detrimental effects from its use and storage. More emphasis has since been placed on the chemical structure using techniques such as pyrolysis-gas chromatography-mass spectrometry (pyr-GC-MS) [14,15], and nuclear magnetic resonance (NMR) spectrometric analysis [16][17][18][19][20][21][22], among others. Interest in lower-grade coal has also increased because of its potential as a soil amendment product which has particular relevance to the work described here.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, few (if any) in situ studies of weathered coal have been undertaken. Even so, we recently showed that outcrop weathered coal was an ideal co-substrate in a bioprocess that utilizes the mutualistic interaction between coal degrading and mycorrhizal fungi and bespoke grasses in the vegetation of discard dumps [20]. Indeed, other forms of weathered coal including coal from discard dumps and a highly oxidized coal obtained from an aged waste dump were unable to support fungal-plant bioremediation and revegetation [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation